Potential Diversity of Natural Regeneration in Peat Swamp Forest: A Case Study at Forest for Specific Purpose (KHDTK) Tumbang Nusa, Central Kalimantan - Dony Rachmanadi; Eny Faridah; Peter J Van Der Meer (Jurnal Ilmu Kehutanan)
Degradation of forest ecosystem including peat swamp forest is generally represented by the degradation of its vegetation cover. Forest degradation tends to follow edge-to-interior distance gradient. This study aimed to determine the diversity and dominance of natural regeneration potential in peat swamp forest at Central Kalimantan. Seedling bank, seed rain, and seed soil bank as the indicators of natural regeneration potential were measured from series of plots located following the distance gradient. The results showed that the difference in natural regeneration potentials followed the distance gradient significantly. The diversity of natural regeneration potential tends to decrease following disturbance gradient, where the lowest was found near the edge. Seedling bank at the edge was dominated by Combretocarpus rotundatus (Miq.) Danser while Litsea oppositifolia L.S. Gibbs dominated at the interior. The seed rain was dominated by Combretocarpus rotundatus at all sites during dry season while during intermediate season, Palaquium sp. dominated the interior and Combretocarpus rotundatus near the edge. It was showed that climatic season gave significant effects on seed number, species number, and diversity of seed rain in which all the three regeneration indications were higher during intermediate season. The seed soil bank was dominated by Tristaniopsis obovata (Benn.) Peter G. Wilson & J.T. Waterh near to the interior and by Diospyros sp. at the edge. However, seed soil banks at the edge zone were dominated by species composing the interior forest (50% similarity index). This shows that the seed dispersal from forest as inoculum source can still reach the edge and also indicates existing vegetation at the edge prior to disturbance.